The Romanian population’s access to education during 1990-2010 - Stefanescu, Maria Livia (Journal of Community Positive Practices, 2020)
In the present article, we will analyze the thematics QAFE, which means the Romanian population’s access to the desired forms of education during 1990-2010. The data used in the current study represent the answers of the Romanians to the question QAFE present in 13 representative samples at national level (the database DQLR-RIQL). Concretely, we will use categorial data of ordinal type. We intend to create a classification of the years from the period 1990-2010, from the point of view of the QAFE problematics. In this way, in a first approach we have used the partial relation “ £os “ of stochastic order which applies to ordinal categorial variables. We have extended the analysis on the thematics QAFE by proposing the indicator PSA of “progress” in order to create a hierarchy of the years from the period 1990-2010 with regard to Romanians’ perception on the aforementionned aspect. The present study shows a permanent change of Romanians’opinions regarding their access to the current forms of education. Among other causes, this aspect is generated by the lack of coherence in the promotion in the educational system from Romania of educational policies that are stable and efficient in the long term.